تأثير العمر، الجنس وبعض العوامل الجينيّة على شدة التهاب النسج حول السنيّة المزمن عند مرضى سوريين - حداد, شادي; أبو سليمان, علي; كفى, فاتن (Latakia University Journal -Medical Sciences Series, 2018)
إنّ التهاب النسج حول السنيّة المزمن مرضٌ إنتانيّ،يتّصف بالتهابٍ لثويّ يمتدّ إلى النسج حول السنيّة المجاورة، مؤدياً لتشكل جيوب حول سنيّة،وخسارة في الارتباط السريري، والعظم السّنخيّ المجاور،يحدث غالباً عند البالغين، ولكن يمكن مشاهدته في أيّ عمر،ويتأثّر معدّل تطوّر المرض بالعوامل الموضعية و/أو الجهازية، والبيئيّة، التي تعدّل استجابة الثوي المناعيّة تجاه اللويحة البكتيريّة، مايزيد الحساسيّة تجاه المرض،ويُعتقد أن الاستعداد للمرض حول السني يرتبط جزئياً بالاستعداد الجيني، وقد تمّ تحديد العديد من الجينات التي تعتبر مواضع كامنة للاستعداد للالتهاب، وأحد أهمها مستقبل الفيتامين د VDR الذي يتواسط فعالية الفيتامين د الحيوية في استقلاب العظم، وتعديل الاستجابة المناعيّة. هدفت دراستنا للتحرّي عن علاقة العمر، الجنس،والتعدّد الشكلي FokI في جين مستقبل الفيتامين د بالحالة السريريّة لمرضى سوريين بالتهاب النسج حول السنيّة المزمن، حيث شملت العيّنة على 50 مريضاً بمتوسط عمر (0.722±64)عاماَ، و30 حالة شاهدة (0.63±50) عاماَ، وتمّ عزل الدنا DNA من الدم المحيطي، وإجراء تفاعل البوليميراز التسلسلي PCR، وهضم شدف الدنا المضخّمة بأنزيم قطع FokI. أظهرت دراستنا بتطبيق اختبار كاي مربع Chi-square عدم وجود فروقٍ يعتدّ بها إحصائياً بين مجموعتيّ الدراسة من حيث العمر، الجنس، وتوزع الأنماط الجينيّة والأليلات في الموقع FokI من جينVDR،وضمن حدود هذا البحث بمكن القول أنّ هذه العوامل لا تؤهّب لحدوث المرض، أو تؤثّر على درجة تطوّره. Chronic periodontitis (CP) is an inflammatory disease, characterized by gingivitis, and affecting tooth supporting tissues, forming periodontal pockets with associated attachment loss, alveolar bone resorption. It is common in adults, but can also occur at any age. The rate of disease progression may be influenced by local, systemic conditions, and/or environmental factors that alter the normal host response to bacterial plaque, and affect the susceptibility to disease.It is suggested that periodontitis is partially associated by genetic factors, that many genes are involved in inflammation susceptibility, mainly include the vitamin D receptor (VDR) gene that is implicated in bone metabolism and the host immune response. 80 Syrian subjects were recruited for vitamin D receptor gene polymorphism study, and allocated in two groups: 50 diagnosed with CP and mean age was (64 ± 0.722) years, 30 matched controls. DNA was isolated from peripheral blood cells, and genotyping was performed by polymerase chain reaction (PCR) method and restriction fragment length polymorphism analysis (RFLP) by using FokI enzyme. By using Chi square test, no significant differences were found between the study groups in the frequencies of alleles and genotypes at FokI position of VDR gene, age and sex. These findings suggest that the investigated factors are not associated with periodontal disease in this studied sample of Syrian population.